Palm oil expansion in Malaysia and its countermeasures through policy window and biorefinery approach - Hassan, Mohd Ali; Ahmad Farid, Mohammed Abdillah; Zakaria, Mohd Rafein; Ariffin, Hidayah; Andou, Yoshito; Shirai, Yoshihito (Elsevier, 2024)
Time and again we hear of calls made by countries to ban palm oil over deforestation. Pressing on, the critics demand the commodity be certified as per international standards and the cultivation to comply with responsible agroecological practices. This urgent and growing concern requires the rethinking of the current operations to be restructured in such a way that it would be cleaner and greener. The Malaysian government has reaffirmed its commitment to mainstream palm oil sustainability by fully embracing United Nation Sustainable Development Goals (SDGs), following through on the 12th Malaysian Plan (2021–2025). Malaysian industry players and stakeholders also have joined hands to pursue the Roundtable on Sustainable Palm Oil (RSPO) and/or Malaysian Sustainable Palm Oil (MSPO) certification with full traceability, as part and parcel of corporate sustainability. However, downstream activities have yet to be improved. The biorefinery concept is proposed to utilize excess resources at plantations and the mills into a wide range of bioproducts and bioenergy in various applications. This review puts together the evidence of technological progress in oil palm biomass valorization, in line with the zero-emission system that will bring this to meet the circular bioeconomy agenda. Also, technological maturity and commercialization of oil palm biomass-derived products are scrutinized, underlining the challenges of the concept proposed.